1982
DOI: 10.1016/s0022-5347(17)54243-3
|View full text |Cite
|
Sign up to set email alerts
|

Distant Metastasis of Renal Adenocarcinoma in Nephrectomized Cases

Abstract: In an analysis of the autopsy records of 1,828 patients with renal adenocarcinoma 424 nephrectomized and 1,404 nonnephrectomized cases were compared to explore the effect of nephrectomy on metastasis. Over-all, no significant difference was observed except for a high incidence of metastases to the brain and femur, and a low incidence of metastases to the ipsilateral adrenal and renal hilar lymph nodes in nephrectomized cases. No significant difference was seen between the nephrectomized and nonnephrectomized c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
78
0
11

Year Published

1984
1984
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 162 publications
(89 citation statements)
references
References 12 publications
0
78
0
11
Order By: Relevance
“…The contralateral adrenal grand, which was biopsied in the patient, was a rare site of metastasis of RCC, being detected in 2.5% of patients with metastatic RCC at autopsy (2). The spread of RCC to the contralateral adrenal gland in the present case may not have been a recent event since a previous study by Lau et al (12) reported that the mean interval to developing contralateral adrenal metastasis following radical nephrectomy is 5.2 years (12).…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…The contralateral adrenal grand, which was biopsied in the patient, was a rare site of metastasis of RCC, being detected in 2.5% of patients with metastatic RCC at autopsy (2). The spread of RCC to the contralateral adrenal gland in the present case may not have been a recent event since a previous study by Lau et al (12) reported that the mean interval to developing contralateral adrenal metastasis following radical nephrectomy is 5.2 years (12).…”
mentioning
confidence: 54%
“…Around 20% of patients experience recurrence or develop metastatic RCC following nephrectomy (1). Although late recurrence of RCC following curative initial surgery is not a rare event, a previous study demonstrated that contralateral adrenal metastasis of RCC is rare (2). Endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) is a relatively novel modality for obtaining samples from deep-seated lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, contralateral adrenal involvement in RCC is extremely rare. In an autopsy study made with > 400 RCC patients who had undergone nephrectomy, contralateral adrenal gland was the only site of metastatic involvement in only 2.5% [2]. Saitoh et al's study made in order to study the frequency of metastasis in RCC patients with a series of 1,828 autopsies revealed that solitary and synchronous CAM was seen only in 0.19% of the patients [2].…”
Section: Discussionmentioning
confidence: 99%
“…In an autopsy study made with > 400 RCC patients who had undergone nephrectomy, contralateral adrenal gland was the only site of metastatic involvement in only 2.5% [2]. Saitoh et al's study made in order to study the frequency of metastasis in RCC patients with a series of 1,828 autopsies revealed that solitary and synchronous CAM was seen only in 0.19% of the patients [2]. Another retrospective study made with 610 radical nephrectomy cases has shown that CAM incidence was 1.1% [11] and that all metastases to the contralateral adrenal glands were clear cell tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation